Effect of Extract Combination Tithonia diversifolia (Hemsley) A.Gray and Curcuma domestica Val. In Function of Heart and Kidney Rats of Cancer Model - Angga Anugerah; Woro Rukmi Pratiwi; Mae Sri Hartati Wahyuningsih (Majalah Farmaseutik, 2018)
Both Tithonia diversifolia (Hemsley) A. Gray leaves and (Curcuma domestica Val.) rhizome have bioactive compound which are an anticancer drug candidate. However, in vivo study about the effect of those to liver function and kidney function has never been carried out. The aim to determine the effect of ethanol extract T. diversifolia (Td) and C.domestica (Cd) combination to Sprague Dawley female rats liver and kidney function which have been induced with DMBA. This research used a quasi experimental study design. There were 31 female rats divided into 6 groups; healthy group; doxorubicin group; breast cancer model; extract combination I (n=5), extract combination II (n=5), extract combination III (n=5). DMBA used to initiate breast cancer was given twice a week for 5 weeks. After palpable breast cancer was showed up, the combination extract groups were given ethanol extract combination of kembang bulan leave and turmeric rhizome twice a day for 4 weeks orally with dosage ratio 40:150 mg/kgBW, 80:150 mg/kgBW, 160:150 mg/kgBW, respectively. Doxorubicin group was given 0,032mg/20gBW intraperitoneally once a day for 4 weeks. Liver and kidney function test were conducted on day 0 and the last day with SGOT, SGPT, Ureum and Creatinine level as the parameters measured. Comparison of liver and kidney function test results between extract combination groups and control groups showed no significant difference. The parameters measured were SGOT (p=0,847), SGPT (p=0,237), Creatinine (p=0,671), Ureum (p=459). Extract combination groups compared to control groups have no significant effect to liver and kidney function.